A Rare Presentation of Unilateral Retinitis Pigmentosa: A Case Report and Review of the Literature. - McCurdy, Alexis (Optometry & Visual Performance, 2025)
Background: Retinitis pigmentosa (RP) is one of the most common inherited diseases of the retina, affecting 1 in 4,000 individuals. This condition occurs when there is deterioration in the photoreceptors, leading to a gradual decrease in vision. The typical progression and presentation of RP includes night blindness, photophobia, progressive deterioration of visual fields, reduced electroretinogram amplitudes, and a decrease in visual acuity. There is, however, a small number of reported cases of unilateral retinitis pigmentosa. This paper will review a case of potential unilateral retinitis pigmentosa in a child and discuss differential diagnoses and diagnostic methods. Case Report: An 11-year-old AA male presented with mild decreased vision OS that was correctable to 20/20. On objective exam, anterior segment was unremarkable and posterior segment was remarkable for a bone spicule-like appearance in the superior temporal quadrant OS. The patient returned to clinic for fundus autofluorescence, visual field testing, and electroretinogram testing. These tests showed asymmetric responses between the right and left eyes, with the left eye being reduced. Conclusion: Although RP presents similarly in most patients, this paper will discuss differential diagnoses for a unilateral RP diagnosis. Different diagnostic methods, such as fundus autofluorescence, electroretinogram (ERG), optical coherence tomography (OCT), and visual field testing are useful in diagnosing and managing these patients.